Characterization of Complementary Determinant Region 3δ in Human MutS Homologue 2‐Specific γδ T Cells. (February 2015) - Chen, H.; Ji, X.; Cui, L.; Zhang, J.; He, W.
Abstract γδT cells function as sentinels in early host responses to infections and malignancies. Previously, we found ectopically expressed human MutS homologue 2 (hMSH2), recognized by γδT cells, triggered a γδT cell‐mediated cytolysis to tumor cells. However, the characteristics of hMSH2‐specific γδ Τ cells are not fully understood. In this study, we investigated the complementary determinant region (CDR) 3δ diversity of hMSH2‐specific γδ T cells. We found that the CDR3δ sequences of hMSH2‐specific γδ T cells displayed limited diversity, while the length and germline gene usage showed no differences compared with whole CDR3δ immune repertoire. There are more hydrophilic amino acids in P/N insert of hMSH2‐specific γδ T cells including the more conserved amino acid at the position 97. Our results offer clues to understanding antigen recognition pattern of γδ T cells to stress‐induced hMSH2 of tumor cells and also the mechanism of γδT cell‐mediated tumor immune surveillance.